Assessing fetal health by pregnant women in China using mobile health application - Yu, Xinxin; Ramli, Saiful Hasley; Mohad Norowi, Noris; Surip, Siti Suhaily; Ibrahim, Rahinah; Yang, Xiaolin; Li, Ziming (Asian Scholar Network, 2023)
This study endeavours to tackle the critical problem of inadequate evidence-based content in mobile health applications (mHealth apps), which adversely impact the accuracy of pregnancy outcomes. To this end, a conceptual framework for evaluating the visualization of fetal health is proposed through a systematic literature review method. This research aims to achieve the following objectives: (1) identify crucial health information that pregnant women in China need to know, (2) determine the best mHealth apps for pregnant women in China, and (3) evaluate the key components for assessing fetal health using mHealth apps among pregnant women in China. The results include fetal health variables, pregnancy complication variables, healthy diet variables, self-care practice variables, and user interface variables. This study contributes to proposing a design of mHealth apps by generating evidence-based visualized fetal assessment methods to foster prenatal attachment and reduce adverse pregnancy outcomes. This study presents a theoretical framework for mHealth apps aimed at pregnant women.